Rescheduling electricity demands in domestic buildings - Deering, Stuart (Cranfield University, 1995)
Utilisation of electricity within the domestic sector is examined. The characteristically time-dependent behaviours o f domestic consumers and their associated usages of household appliances, result in "peaky" daily electricity-demand curves. This is not conducive to achieving (i) a high-efftciency electricity supply, (ii) low rates o f financial investment in new generating plant or (iii) curtailing rates of pollutant emissions. A relatively energy-efficient, environmentally-clean, electricity-supply system can only be realised when the total demand (i.e. the total for the domestic, commercial and industrial sectors) versus time curve does not exhibit rapid changes in gradient. In order to achieve this goal, existing and more appropriate electrical-load management techniques need to be implemented, especially for the domestic sector. Thus opportunities fo r demand-side load-management are assessed together with the prospective benefits obtainable by domestic consumers and electricity-supply companies. The operation o f appliances, which are significant contributors to the typical daily household electricity-demand profile, are examined in detail. Demand profiles for individual appliances are presented and, where appropriate, examples of thermal, motive and control sub-profiles are provided. Patterns of appliance use within households are discussed with various recommendations for achieving reduced load profiles, both for specific appliances and households.